Uroflujometry in the study of low urinary tract symptoms in male patients. Hospital Central Universitario Dr. Antonio María Pineda (Boletin Médico de Postgrado, 2020)
Uroflowmetry is a non-invasive study of the lower urinary tract that provides objective information on urinary flow and is widely recommended by European guidelines for the study of patients with lower urinary tract symptoms. We performed a cross-sectional descriptive study to describe the use of uroflowmetry for the study of lower urinary tract symptoms in males who attended the Servicio de Urología of the Hospital Central Universitario Dr. Antonio María Pineda (Barquisimeto, Lara state) during the 2018- 2019 period. The sample was made up of 150 males. The results show that 62% of the sample included males between 60 and 70 years old and 52% complained of mild urinary symptoms. Uroflowmetry results showed that 56% of patients had a maximum flow between 10 and 20 ml/sec suggestive of urinary tract obstruction; 78% had an average flow between 0 and 10 ml/sec while 53% had a micturition volume < 300 ml and 49% had a maximum flow time between 30 and 50 seconds. Uroflowmetry is a simple and fast test which provides useful information about the health of lower urinary tract.
Keywords: uroflowmetry; lower urinary tract; micturition; urinary symptoms; incontinence